التحري الفعال للمراجع الخارجي عن احتيال الإدارة في التقرير المالي - حمزة محي الدين; الغصين راغب; جديني رشا فتحي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن تقييم الخطر هو عملية مراجعة وتحليل شاملة للشركة لتقرير مكان وجود المخاطر ونمط الإجراءات التصحيحية المطلوبة. يساعد هذا التقييم المدقق على تحديد واستهداف مناطق الخطر العالي. والاحتيال استراتيجي في طبيعته، ويتضح هذا في تأثر نزعة الإدارة لارتكاب الاحتيال بالمراجعة المتوقعة وتأثر نهج المراجع في كشف الاحتيال بمدى ودرجة احتمال ارتكاب الإدارة للاحتيال. فالتفكير في السياق الاستراتيجي لكشف الاحتيال يعتمد على نظرية اللعبة، حيث تسعى هذه النظرية للتنبؤ بسلوك الفرد اعتماداً على أفضل استجابة لذلك الفرد والتي يحددها: حوافز ودوافع الفرد + توقعات الفرد لسلوك خصمه المحتمل. إن أخذ المراجع بالاعتبار لرد فعل الشركة الخاضعة للتدقيق تجاه خيارات المدقق هو ما يعرف بالتفكير الاستراتيجي. بناء عليه، سيتم تطوير مناهج الاحتيال في القوائم المالية بالشكل الذي سيفشل معه نهج المراجعة النمطي للمدقق في اكتشافها. وسيستخدم المراجع الفعال التفكير الاستراتيجي لأجل التحري الفعال عن ذلك النشاط الاحتيالي. أي أن المدقق سينفذ إجراءات غير متوقعة وسيستخدم اختبارات لم يسبق أن شهدتها الإدارة. A risk assessment is a comprehensive review and analysis of a company to determine where the risks are and the type of corrective actions needed. Such an assessment helps auditors to target areas with high risks. Fraud is strategic in nature such that management’s propensity to commit fraud is affected by anticipating audit and the auditor’s approach to detecting fraud is affected by the potential for committing fraud by management. The thinking involved in a strategic setting such as the detection of financial statement fraud is based on a game theory, which seeks to predict behavior based on an individual’s best response determined by that individual’s motivations and beliefs and their anticipation of the opponent’s likely behavior. The auditor’s consideration of an auditee’s response to auditor choices is referred to as "strategic reasoning". As a result, financial statement fraud schemes will be developed in a way that prevents them from detection by the auditor’s typical audit approach. And the effective auditor will use strategic reasoning to effectively detect this fraudulent activity. In other words, the auditor will perform unexpected procedures and use tests that management has not seen before.